Yao medicine Amydrium hainanense suppresses hepatic fibrosis by repressing hepatic stellate cell activation via STAT3 signaling - Wu, Bingmin; Huang, Lan; Wang, Yange; Zeng, Lishan; Lin, Ying; Li, Jingyan; Wang, Shaogui; Zhang, Guifang; An, Lin (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Hepatic fibrosis (HF) occurs in response to chronic liver injury and may easily develop into irreversible liver cirrhosis or even liver cancer. Amydrium hainanense water extract (AHWE) is a water-soluble component extracted from the Yao medicine Amydrium hainanense (H.Li, Y.Shiao & S.L.Tseng) H.Li, which is commonly used for treating inflammatory diseases in folk. Previous evidence suggested that AHWE significantly inhibited hepatic stellate cell activation. However, little is known regarding the therapeutic effect of AHWE in HF and its underlying action mechanism. Objective: Investigation of the therapeutic effect of AHWE in HF and its underlying mechanism. Methods: The therapeutic effect of AHWE was tested in vivo using an HF mouse model via an intraperitoneal injection of carbon tetrachloride (CCl4). Histological evaluation of liver injury and fibrosis were tested by H&E staining and Masson’s trichrome staining. Serum levels of ALT, AST, collagen type I (Col I), and hydroxyproline (HYP) were measured. The mRNA expression of liver fibrotic and inflammatory genes were tested, and the protein levels of alpha smooth muscle actin (α-SMA) and signal transducers and activators of transcription 3 (STAT3) were analyzed. The in vitro experiments were conducted using HSC-T6 and RAW264.7 cell lines. Results: Treatment with AHWE significantly reversed histopathological liver damage and liver function abnormalities in CCl4 mouse model. Also, the serum levels of ALT, AST, Col I, and HYP in CCl4-induced HF mice were improved in AHWE treatment. Further, AHWE showed a remarkable inhibitory effect on the expression of fibrosis markers (Acta2, Col1a1, and Col3a1) and inflammatory factors (Stat3, Tnfa, Il6, and Il1b) induced by CCl4. The results of in vitro experiments were consistent with those obtained in vivo. In addition, it is shown that STAT3 signaling was involved in the anti-fibrotic effects of AHWE as evidenced by STAT3 overexpression. Conclusion: The present study proposed a novel ethnomedicine for HF and suggested the underlying role of STAT3 signaling pathway regulation in this anti-fibrotic effect of the proposed medicine. These findings would serve as solid scientific evidence in support of the development of AHWE as a novel alternative or complementary therapy for HF prevention and treatment.